ROLE OF COMPUTER GRAPHICS IN DEVELOPING COGNITIVE COMPETENCES OF STUDENTS (American Journal of Pedagogical and Educational Research, 2024)
In the following article the modern methods of perfection of the cognitive competencies of the students in teaching the lesson of drawing are analyzed based on the available data.